War and Millie McGonigle - Cushman, Karen (Yearling, 2022)
With World War II looming and the lingering economic depression straining her family's finances, twelve-year-old Millie struggles to look for happiness in 1941 California. Determined to find peace along the beach, Millie discovers a new friend, even as she must contend with demands from her younger siblings, an annoying older relative who moves in with them, and the death of her beloved grandmother. Then the Pearl Harbor attack changes everything, and Millie must take on more responsibility as both of her parents return to work amid rumors and prejudice in the community.